2013
DOI: 10.1371/journal.pone.0083105
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Apoptosis Mechanism Induced by T-2 Toxin

Abstract: T-2 toxin is known to induce apoptosis in mammalian cells. The mechanism of apoptosis induced by T-2 toxin has been proposed to be linked with oxidative stress and mitochondrial pathway. In the current study, the toxic effect of T-2 on Hela, Bel-7402, and Chang liver cells was examined in dose-dependent and time-dependent manner by MTT assay. Caspase-3 was found to be up-regulated under T-2 toxin stress, which suggested that T-2 toxin induced cell apoptosis. Endogenous GSH and MDA levels in all three cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The mitochondria, death receptor and ER‐mediated apoptotic pathways are the three key pathways involved in apoptosis in mammalian cells (Wang et al, ). Zhuang, Yang, Huang, and Wang () reported that the mechanism of apoptosis induced by the T‐2 toxin was linked with oxidative stress and the mitochondrial pathway in Hela, Bel‐7402 and Chang liver cells. In this study, an increased cleaved‐caspase‐3 protein expression was observed upon T‐2 toxin exposure (Figure C).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria, death receptor and ER‐mediated apoptotic pathways are the three key pathways involved in apoptosis in mammalian cells (Wang et al, ). Zhuang, Yang, Huang, and Wang () reported that the mechanism of apoptosis induced by the T‐2 toxin was linked with oxidative stress and the mitochondrial pathway in Hela, Bel‐7402 and Chang liver cells. In this study, an increased cleaved‐caspase‐3 protein expression was observed upon T‐2 toxin exposure (Figure C).…”
Section: Discussionmentioning
confidence: 99%
“…5 T-2 toxin exposure induces lesions in hematopoietic, lymphoid, gastrointestinal, and brain tissue. [6][7][8] Also, T-2 toxin exhibits cytotoxic and immunosuppressive action, 9 causes inhibition of the syntheses of protein, DNA and RNA, 6,7 affects the cell cycle in human chondrocytes C28/12, hepatic epithelial L-02 and tubular epithelial HK-02 cells, 10 and induces apoptosis in fetal rat brain, 6 human chondrocytes, 11 different human cell lines, such as HeLa, Bel-7402, Chang liver cells, 12 human chondrocytes C28/12, hepatic epithelial L-02, and tubular epithelial HK-02 cells. 10 These studies indicate that T-2 toxin induces apoptosis through the reactive oxygen speciesmediated mitochondrial pathway by activating various signaling mediators, such as mitogen-activated protein kinases (MAPK) and caspases.…”
Section: Introductionmentioning
confidence: 99%
“…10 These studies indicate that T-2 toxin induces apoptosis through the reactive oxygen speciesmediated mitochondrial pathway by activating various signaling mediators, such as mitogen-activated protein kinases (MAPK) and caspases. 6,[10][11][12] European Food Safety Authority has established a tolerable daily intake (TDI) of 100 ng/kg body weight (bw) for the sum of T-2 and HT-2 toxins (the main metabolite of T-2 toxin) 13 and still has only recommendation values for their presence in cereals and cereal products within the European Union. 14 A number of studies have indicated adverse effects of T-2 toxin on reproduction and development in animals.…”
Section: Introductionmentioning
confidence: 99%
“…fungus can induce apoptosis -a programmed cell death -of several cell lines of humans and animals [22]. Since T-2 toxin is a main type A trichothecene mycotoxin which is the most toxic trichothecence, it has posed various toxic effects on humans and animals in vigorous cell proliferation tissues like lymphoid, hematopoietic and gastrointestinal tissues [9,21].…”
Section: Introductionmentioning
confidence: 99%